Ophryotrocha (Dorvilleidae, Polychaeta, Annelida) from deep-sea hydrothermal vents, with the description of five new species - Zhang, Dongsheng; Zhou, Yadong; Yen, Nicole; Hiley, Avery S.; Rouse, Greg W. (European Journal of Taxonomy, 2023)
Dorvilleids belonging to Ophryotrocha Claparède & Mecznikow, 1869 are known from deep-sea hydrothermal vents in the Pacific, Atlantic, Indian and Southern Oceans. However, how they colonized and diversified in these ecosystems has not been assessed in detail. Here, a collection of Pacific hydrothermal vent Ophryotrocha was examined using morphology and DNA markers (COI, 16S and H3). Five new species were revealed, largely expanding the diversity of the group at this habitat type. They are Ophryotrocha charlottae sp. nov., O. kailae sp. nov., O. marinae sp. nov., O. pruittae sp. nov. from eastern Pacific, and O. bohnorum sp. nov. from the western Pacific. Phylogenetic analyses based on the concatenated alignments of all three genes suggest vent habitants have been colonized several times independently within Ophryotrocha. One clade of six vent species was recovered, indicative of diversification following a colonization of hydrothermal vents, likely in the eastern Pacific. An Indian Ocean species, O. jiaolongi, was nested inside this clade and was closely related to one of the new species from the Gulf of California, diverging from it by less than 4% on COI.